Hadith #2708 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ibrahim bin Yusuf bin Ishaq إبراهيم بن يوسف بن إسحاق; Yusuf bin Ishaq bin Abi Ishaq يوسف بن إسحاق بن أبي إسحاق (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who believes in Allah and the Last Day must not ride on packhorse belonging to the booty of the Muslims and put it back when he has emaciated it; and he who believes in Allah and the Last Day must not wear a garment belonging to the booty of the Muslims and put it back when he made it threadbare.
Grade: Hasan Sahih

Hadith #5220 - Sunan Abi Dawud - Abdullah bin Salm عبد الله بن سالم; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Bara' bin Azib bin al-Harith; Ibrahim bin Yusuf bin Ishaq إبراهيم بن يوسف بن إسحاق; Yusuf bin Ishaq bin Abi Ishaq يوسف بن إسحاق بن أبي إسحاق (Sunan Abi Dawud)
The Prophet (ﷺ) received Ja’far ibn AbuTalib, embraced him and kissed him between both of his eyes (forehead).
Grade: Da'if

Hadith #2018 - Jami' al-Tirmidhi - Abdur Rahman bin Awsjh عبد الرحمن بن عوسجة الهمداني; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Bara' bin Azib bin al-Harith; Ibrahim bin Yusuf bin Ishaq إبراهيم بن يوسف بن إسحاق; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب; Yusuf bin Ishaq bin Abi Ishaq يوسف بن إسحاق بن أبي إسحاق (Jami' al-Tirmidhi)
“I asked ‘Aishah about the character of the Messenger of Allah. She said: ‘He was not obscene, nor uttering obscenities, nor screaming in the markets, he would not return an evil with an evil, but rather he was pardoning and forgiving.”
Grade: